Pengembangan Media Pembelajaran Digital Melalui Pendekatan Realistic Mathematics Education (RME) Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa Di SMP Negeri 1 Percut Sei Tuan - Elly Nafsiah; Tiur Malasari Siregar (Lembaga Pengembangan Kinerja Dosen, 2023)
This research was conducted with the aim of producing digital learning media using the Smart Apps Creator through a Realistic Mathematics Education approach that is valid, effective, and able to improve students' mathematical problem solving abilities in the matter of a system of two-variable linear equations. This type of research is Research and Development (R&D) with the ADDIE model. From the research results, it was obtained that the media and material validity values were 93.6% and 93% with very valid categories. The practicality of the media through the results of the teacher's response questionnaire obtained a practicality value of 97.3% in the very practical category and the results of the student response questionnaire for the small group test and large group test obtained values of 90.9% and 91.4% in the very practical category. Then the value of effectiveness is seen through the mastery of classical learning and the results of the student response questionnaire obtained percentages of 87.5% and 94.05% with very effective categories. Improving problem solving abilities in students, the results obtained are that the level of students' problem solving abilities is at a percentage of 92% with a very high category, while based on the N-Gain test the average value obtained by students is 0.6473 which means there is an increase in problem solving abilities in students medium category. So based on the results obtained it can be concluded that the learning media developed in this study are valid, practical, effective, and able to improve students' mathematical problem solving abilities.